Action-research: relations with design - Ferreira, Alais Souza; Berlato, Larissa Fontoura; Figueiredo, Luiz Fernando Gonçalves de; Braviano, Gilson (DAT Journal, 2020)
Action research is a methodological strategy of social research that aims action as an intention to change. This action consists of solving or at least clarifying the problems of the observed situation. This method intends to directly involve social groups in the search for solutions to their problems and promotes a greater articulation between theory and practice in the construction of new knowledge. The present article aims to identify the possible contributions of action research in the design process, being characterized as a qualitative, exploratory and descriptive study. This analysis suggests that action research can help to assist the designer in understanding the context; in identifying the needs of the actors involved and the problems of a given situation; in the selection of techniques and tools to be used in the process; in dialogue among all actors; in the analysis and interpretation of the information collected; and in the formulation of a solution in a collaborative or co-creative manner.